The Impact of Taxation On FDI: Comparative Analysis of Romania and Hungary - Fuad BAHRAMOV (Communications of International Proceedings, 2022)
The paper examines the effects of taxation, obviously, tax rates, tax incentives and exemptions on foreign direct investment in two border countries: Hungary and Romania. The main motivation of study is new tax regulations and changes to fiscal codes of selected states in 2022.  Significant role of FDI in economic growth of states obligates to seek for effective methods of attraction of foreign investments and that situation cause to boost up the actuality and popularity of subject which refers to tax and FDI relations. The research used univariate t-test method and general comparison of indicators of FDI inflows and tax rates of both countries. The results explain when tax rates decline, FDI flows increase at univariate level and there is a negative relation between reduced tax rates and foreign investments. This research points out the application of additional special taxes in Hungary in 2022 can demotivate the foreign investors to invest and simultaneously, the new changes to Romanian fiscal code which will be applicable by January 2023 will also affect FDI inflows in Romania, negatively.
Keywords: taxation; tax incentives; tax rates; foreign direct investments.